Primary and preschool immunisation in Grampian: progress and the 1990 contract. Issue 6830 (28th March 1992) - Ritchie, L. D.; Bisset, A. F.; Russell, D.; Leslie, V.; Thomson, I.
Abstract : OBJECTIVE–To examine changes in immunisation performance in Grampian region after the introduction of the 1990 contract for general practitioners. DESIGN–Retrospective descriptive study using data held on the Grampian immunisation record system's computer. SETTING–All 95 general practices in Grampian region (313 general practitioners). PATIENTS–All children in the primary immunisation and preschool booster age groups. This formed two groups of children for each of the four calendar quarters of 1990 and first three quarters of 1991 analysed as (a) those aged 2 years on the first day of the relevant quarter and (b) those aged 5 years on the first day of the relevant quarter, with an average population of 6600 and 6400 respectively. MAIN OUTCOME MEASURE–Percentage immunised by practice. RESULTS–For primary immunisation the number of practices achieving immunisation rates of at least 95% increased from 29 (31%) to 76 (81%), and practices achieving 90% rates rose from 69 (73%) to 87 (93%). For preschool boosters, the number of practices achieving at least 95% immunisation rates increased from 22 (23%) to 61 (64%). By the end of September 1991, 76 (80%) practices were achieving at least 90% levels compared with 36 (39%) at the beginning of 1990. Since the beginning of 1989 the proportion of immunisations not given by general practitioners declined from 14% to 2%. CONCLUSIONS–Primary and preschool immunisation rates for preschool children in Grampian showed a sustained improvement during 1990 and consolidation in 1991. Although overall trends were unchanged, 18 months after the introduction of the 1990 contract only one practice failed to meet lower target levels of 70% for both primary and preschool immunisation. By September 1991 more than three out of four practices had reached levels of at least 95% for primary immunisation.